1991
DOI: 10.1088/0029-5515/31/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Lower hybrid ion heating in the FT-2 tokamak

Abstract: The paper generalizes the results of plasma heating experiments in the FT-2 tokamak. It is shown that the generation of fast ions is associated not with the region of linear transformation, nLH, but with the parametric decay region, nd ≃ (0.3-0.5)nLH. In the narrow zone nd, strongly slowed down waves were observed (by a method relying on enhanced scattering of microwave radiation) at a frequency of about 0.7f0 (where f0 is the frequency of the heating radiation); these waves had a narrow spectrum with a width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The spatial location of the fast ion tail seems to depend upon the density profile (Table 11). On FT-2, passive charge exchange profiles suggested that the tail moves from the edge to the centre with increasing density [172]. Both edge and central profiles have been observed on other tokamaks, but the density dependence was not reported.…”
Section: Lower Hybrid Bandmentioning
confidence: 90%
See 1 more Smart Citation
“…The spatial location of the fast ion tail seems to depend upon the density profile (Table 11). On FT-2, passive charge exchange profiles suggested that the tail moves from the edge to the centre with increasing density [172]. Both edge and central profiles have been observed on other tokamaks, but the density dependence was not reported.…”
Section: Lower Hybrid Bandmentioning
confidence: 90%
“…Without beam injection, many experiments have noted a direct correspondence between parametric decay of the fundamental LH wave and tail formation [158,166,167,171,172,241,2421. In these experiments, the tail develops at a lower density than that predicted for direct ion heating by LH waves (that obey the cold plasma dispersion relation).…”
Section: Lower Hybrid Wavesmentioning
confidence: 99%
“…15). This threshold energy is typically ten times larger than the central ion temperature (Table II), scales with Ti0 [172] and is independent of the RF power [160, 1721. Comparison of different parallel wavelength spectra in WEGA found a lower value of Emin and a more intense tail for higher values of 7211 [164]. The critical density for tail formation depends only weakly upon toroidal field.…”
Section: Lower Hybrid Bandmentioning
confidence: 99%
“…The perpendicular wavenumber kl predicted by the cold plasma dispersion relation was too small for direct interaction between the LH and the beam ions. Without beam injection, many experiments have noted a direct correspondence between parametric decay of the fundamental LH wave and tail formation [158,166,167,171,172,241,2421. In these experiments, the tail develops at a lower density than that predicted for direct ion heating by LH waves (that obey the cold plasma dispersion relation).…”
Section: Lower Hybrid Wavesmentioning
confidence: 99%
See 1 more Smart Citation